Motivations for textbook and learning resource publishing: Do academics want to publish OA textbooks? - Collins, Ellen; Stone, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
The affordability of textbooks and unsustainable commercial models are issues that many libraries face. As an alternative, there is a growing movement in the United States around open and affordable textbooks. However, to date there has been less activity in the UK despite the introduction of a range of policies that encourage or mandate open access publication of research outputs such as journal articles or monographs. These policy changes have affected academics’ attitudes to open access, but it is not yet clear whether the opportunity to publish in open access would affect researchers’ propensity to create non-research outputs such as textbooks and learning materials. In 2017, Jisc Collections proposed a study into author incentives for textbook publishing in order to understand whether open access would motivate authors to publish learning materials and thereby support a transition to open access for e-textbooks. The study consisted of a survey, focus groups and interviews. This article discusses the results of the research and provides several key insights and future opportunities for those wishing to explore open and affordable textbooks.